Left-Sided Reoperations After Arterial Switch Operation: A European Multicenter Study - Vida, Vladimiro L; Zanotto, Lorenza; Zanotto, Lucia; Stellin, Giovanni; European Congenital Heart Surgeons Association (ECHSA) Study Group; Padalino, Massimo; Sarris, Georges; Protopapas, Eleftherios; Prospero, Carol; Pizarro, Christian; Woodford, Edward; Tlaskal, Thomas; et al. (The Annals of thoracic surgery, 2017)
BACKGROUND: We sought to report the frequency, types, and outcomes of left-sided reoperations (LSRs) after an arterial switch operation (ASO) for patients with D-transposition of the great arteries (D-TGA) and double-outlet right ventricle (DORV) TGA-type. METHODS: Seventeen centers belonging to the European Congenital Heart Surgeons Association (ECHSA) contributed to data collection. We included 111 patients who underwent LSRs after 7,951 ASOs (1.4%) between January 1975 and December 2010. Original diagnoses included D-TGA (n = 99) and DORV TGA-type (n = 12). Main indications for LSR were neoaortic valve insufficiency (n = 52 [47%]) and coronary artery problems (CAPs) (n = 21 [19%]). RESULTS: Median age at reoperation was 8.2 years (interquartile range [IQR], 2.9-14 years). Seven patients died early after LSRs (6.3%); 4 patients with D-TGA (5.9%) and 3 patients with DORV TGA-type (25%) (p = 0.02). Median age at last follow-up was 16.1 years (IQR, 9.9-21.8 years). Seventeen patients (16%) required another reoperation, which was more frequent in patients with DORV- TGA type (4 of 9 [45%]) than in patients with D-TGA (13 of 95 [14%]). Late death occurred in 4 patients (4 of 104 [3.8%]). The majority of survivors were asymptomatic at last clinical examination (84 of 100 [84%]). CONCLUSIONS: Reoperations for residual LSRs are infrequent but may become necessary late after an ASO, predominantly for neoaortic valve insufficiency and CAPs. Risk at reoperation is not negligible, and DORV TGA-type anatomy, as well as procedures on the coronary arteries, were significantly associated with a higher morbidity and a lower overall survival. Recurrent reoperations after LSRs may be required.
Keywords: Aortic Valve Insufficiency; reoperace; Retrospective Studies; kojenec; Europe; Incidence; Prognosis; mladiství; Evropa; mužské pohlaví; Arterial Switch Operation; Infant; dvojvýtoková pravá komora; incidence; míra přežití; Transposition of Great Vessels; Postoperative Complications; Reoperation; dítě; Follow-Up Studies; Child; následné studie; Child, Preschool; transpozice velkých cév; ženské pohlaví; prognóza; retrospektivní studie; předškolní dítě; Humans; Survival Rate; Double Outlet Right Ventricle; korekce transpozice velkých arterií; rizikové faktory; aortální insuficience; Female; Risk Factors; Adolescent; pooperační komplikace; lidé; Male